Exploring Happiness at Work among Female Workers in a Male-Dominated Nickel Smelter Industry: A Qualitative Case Study from Central Sulawesi, Indonesia - Komang Tri Meika Sari; Rosita Endang Kusmaryani; Friska Juliana Putri Saragih (Da'wa Faculty of Islamic State University Salatiga, 2026)
Happiness at Work is increasingly recognized as central to employee well-being, yet its construction within male-dominated heavy industry remains underexplored. This study examines how happiness at work is experienced by female workers in a nickel smelter industry in Central Sulawesi, Indonesia. Using a qualitative case study design, in-depth interviews were conducted with two female employees working within a high-risk and masculine organizational context. Data were analyzed through iterative coding informed by grounded theory procedures. The findings indicate that happiness at work is relationally constructed through interconnected dynamics: professional recognition and empowerment, supportive social relationships, engagement in challenging tasks that foster flow, and adaptive responses to organizational and operational pressures. Rather than representing the absence of stress, happiness emerged as a negotiated psychological experience shaped by competence validation, belonging, and resilience within demanding industrial conditions. As a context-specific case inquiry, this study provides situated insight into women's lived experiences and underscores the importance of inclusive supervisory practices and gender-sensitive organizational support in heavy industry.